2016
DOI: 10.5824/1309-1581.2016.1.001.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Five-Factor Model of Personality Traits on Turnover Intention among Information Technology (IT) Professionals

Abstract: This study aims to identify the factors affecting turnover intention among IT professionals. A model was developed with the inclusion of five-factor model of personality traits, job satisfaction, career satisfaction, career self-efficacy and career commitment. A total of 430 responses were gathered from IT professionals working in Turkey. Structural equation modeling technique was used for the analysis. According to the results, job satisfaction and career commitment have direct negative effects on turnover in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Although not directly hypothesized, concerning the direct effects of personality traits on job satisfaction, we found a positive relationship for conscientiousness and a negative relationship for neuroticism in line with other studies made in Turkey (Camgoz & Karapinar, 2011;Gümüşsoy, 2016). More specifically, congruent with prior research, our findings demonstrate that individuals who are high in conscientiousness report higher levels of job satisfaction (Winkelmann & Winkelmann, 2008;Templer, 2012), whereas individuals who are high in neuroticism report lower levels of job satisfaction (Connolly & Viswesvaran, 2000;Judge, Heller, & Mount, 2002;Kim & Chung, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although not directly hypothesized, concerning the direct effects of personality traits on job satisfaction, we found a positive relationship for conscientiousness and a negative relationship for neuroticism in line with other studies made in Turkey (Camgoz & Karapinar, 2011;Gümüşsoy, 2016). More specifically, congruent with prior research, our findings demonstrate that individuals who are high in conscientiousness report higher levels of job satisfaction (Winkelmann & Winkelmann, 2008;Templer, 2012), whereas individuals who are high in neuroticism report lower levels of job satisfaction (Connolly & Viswesvaran, 2000;Judge, Heller, & Mount, 2002;Kim & Chung, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Besides paternalistic leadership, these behaviours are compatible with the dimensions of transformational leadership. In fact, recent studies reported that transformational leadership is the most preferred leadership style in Turkey (Aycan & Fikret-Pasa, 2003; Gumusluoglu & Ilsev, 2009; Gumusluoglu, Karakitapoğlu-Aygün, & Hirst, 2013). As in other countries, much of the interest has been devoted to investigate the prevalent and preferred leadership styles in Turkey; however, less attention has been directed to the investigation of how these leadership styles affect employee’s perceptions such as perceived empowerment and job satisfaction.…”
Section: Cultural Values and Business Context In Turkeymentioning
confidence: 99%
“…On the other hand, previous research in the IT industry indicates that conscientiousness is positively associated with knowledge sharing behaviour (Hao et al. , 2019) and with career self-efficacy (Gümüşsoy, 2016). It is also noteworthy that conscientiousness is positively associated with technostress, that is to say, stressors related to the use of IT (Korzynski et al.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Individual, environmental, and organizational factors play a role in the emergence of TOI (Jha, 2009;Oliveira, Gomide Júnior, Poli and Oliveira-Silva, 2018;Puhakka, Nokelainen and Pylväs, 2021). In literature, personality traits are the leading factors to explain TOI (Jeswani and Dave, 2012;Gumussoy, 2016). Literature studies have commonly explored the association between typical personality traits and TOIs using the Big Five framework (Yang, Gong and Huo, 2011;Ariyabuddhiphongs and Marican, 2015;Saoula, Johari and Bhatti, 2016).…”
Section: Introductionmentioning
confidence: 99%